Fungal Community profile of Zygopetalum maxillare and Zygopetalum mackayi (ORCHIDACEAE) - Veloso, Tomás Gomes Reis (2016)
The orchids seeds are minute and easily dispersed by the wind. However, due to this reduced size there is no enough reserve tissue to allow seed germination, so that the nutrients uptake in the in the first steps of life cycle is done by the association to a mycorrhizal fungus. Once distinct orchids species associate can associate with distinct fungi is important to know for each orchid which are the fungi associate, because the conservation of threatened orchids requires the conservation of the fungi. Here, culture-depedent and independent on approaches were used for studying the fungal profile community of two orchid species, Zygopetalum maxillare, an epiphyte, and Zygopetalum mackayi, a terrestrial. The results of culture-independent methods showed fungi of Ascomycota as the majority present. Both Zygopetalum species associate with Sebacinaceae and Ceratobasidiaceae, however, while species of Ceratobasidiaceae are shared by both orchids, Sebacinaceae are not. These results were corroborated by the results of culture-dependent approaches, although no fungi of Ceratobasidiaceae could be isolated. The isolates obtained by this study are potential to be used in seed germination and seedling development of Z. maxillare and Z. mackayi and for future use in reintroduction program.